Glass Ceiling and the Aspirations of Lady CPAs in Public and Private Organizations - Herrero, Carmen; Marasigan, Rowell; Magsino, Renilda (Social Sciences and Development Review, 2023)
This feminist qualitative research that made use of exponential non-discriminative snow-ball sampling was conducted using “open-ended questions on questionnaire” to explore the deeper insights of women Certified Public Accountants (CPAs) in private and public offices.The themes that emerged from the data collected include: 1) confidentiality in pay that reduces transparency in determining level in the organizational hierarchy, 2) confidence and assertiveness of lady CPAs could contribute to professional skepticism which is crucial in detecting fraud and errors, and 3) flexible working hours not enjoyed. It was also confirmed that programs and policies for the well-being of women employees are available and in place, both in private and public organizations. Another issue that emerged is that the theory of glass ceiling still exists after a long time since it was first introduced. Aspirations and dreams of lady CPAs are varied, ranging from trivial to significant. The significant aspirations include hopes for gender and leadership diversity, mentoring, and mobility.
Keywords: Glass Ceiling Theory; mentoring programs; exponential non-discriminative snowball sampling; gender and development